Determinants of the Supply of Women in the Labour Market: A Micro Analysis (The Pakistan Development Review, 1991)
Neoclassical economists consider education to be one of the key determinants of women entering the labour market. The higher the level of education, the greater is women's participation in the labour market. [Becker (1980); Mincer (1980)]. However, the structuralist school does not look at it so simply. In their view there are many other factors besides education which compel women to· sell their labour power. [Benham (1980); Strober (1980)]. The principal factor compelling women to sell their labour is income. Therefore, according to the structuralist school the lower is women's household income, the greater is their compulsion to enter the labour market. How does this square with neoclassical theory? The structuralist school states that household income is the primary determinant of women's sale of labour power. Therefore, in a society divided by income groups lower income class women will tend to sell their labour power more. However, within each income group an increase in education will increase the supply of women's labour and its returns. Due to inadequate data, relatively little analytical work on this issue has been undertaken so the present study is an attempt to explore why some married women are engaged in earning activities, while some of them are not. Our sample consists of ever-married women, because normally they are considered independent, and their status is equal to their male partners. So they have relatively more choice in entering the labour market compared to unmarried women. A comparison of this kind will help us to identify the factors besides education in determining women's supply of labour in the market.